Skema Peningkatan Reciprocity Kanal dengan Menggunakan Metode Hierarchical Clustering - Prima Kristalina; Florista Dewi; Mike Yuliana; Tri Budi Santoso; Amang Sudarsono; Reni Soelistijorini (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2018)
Secret key generation scheme that utilizesthe randomness of wireless channels is a very promising alternative to establish a secure communication path. Some wireless devices are used to obtain the channel parameters. But the problem that occurs is imprecise measurement results, causinga secret key difference between the two users. To overcome this problem, pre-processing method is used before the data is quantized, to increase the similarity (reciprocity) channel parameter measurement results. In this paper, the effect of the use of one pre-process method, which was hierarchical clustering, on the performance of secret key generation scheme in an indoorenvironment with two variations of scenario was investigated.The results show that the use of the pre-processingmethod can improve the similarity parameter of the channel measurement results as indicated by the increasing of correlation values up to 20%. In addition, the resulting bit mismatch also decreases with the value of key disagreement rate (KDR) maximum of 20%.